Effects of Vertical Movement of the Anterior Nasal Spine on the Maxillary Stability After LeFort I Osteotomy for Pitch Correction. Issue 6 (September 2015) - Ohba, Seigo; Nakao, Noriko; Nakatani, Yuya; Yoshimura, Hitoshi; Minamizato, Tokutaro; Kawasaki, Takako; Yoshida, Noriaki; Sano, Kazuo; Asahina, Izumi
Abstract : Abstract: Few reports have so far evaluated the maxillary stability after LeFort I osteotomy (L-1) for pitch correction. In the current study, the authors assessed the SN-PP (palatal plane) to evaluate the skeletal stability after osteotomy with clockwise or counter-clockwise rotation and investigated the effects of anterior nasal spine (ANS) and posterior nasal spine (PNS) movement on the stability of the SN-PP. The SN-PP and the positions of ANS, PNS, and point A were measured on lateral cephalograms before surgery (T1), immediately after surgery (T2), and more than 1 year after surgery (T3). All measured angle and points were stable in 4 cases of counter-clockwise rotation. In the 16 cases of clockwise rotation, T3-T2 of SN-PP, ANS, and point A was −2.05°, −2.56 mm, and −1.64 mm, when the SN-PP increased more than 4° after osteotomy. When the ANS moved downward more than 3 mm, the ANS and point A relapsed significantly by 2.75 and 2.31 mm, while the SN-PP relapsed 1.61° more than 1 year after surgery. When the SN-PP increased by more than 4° or the ANS moved downward by more than 3 mm, the authors suggest shifting the PNS upward instead of moving the ANS downward.